Higher Glucocorticoid Secretion in the Physiological Range Is Associated With Lower Bone Strength at the Proximal Radius in Healthy Children: Importance of Protein Intake Adjustment. (February 2015) - Shi, Lijie; Sánchez‐Guijo, Alberto; Hartmann, Michaela F; Schönau, Eckhard; Esche, Jonas; Wudy, Stefan A; Remer, Thomas
ABSTRACT Whether higher production of glucocorticoids (GCs) within the physiological range may already be affecting bone status in healthy children is unknown. Because dietary protein intake affects both bone and GCs, we examined the association of urinary measures of glucocorticoid status and cortical bone in healthy non‐obese children, after particularly controlling for protein intake. Proximal forearm bone parameters were measured by peripheral quantitative computed tomography (pQCT). Subjects studied (n = 175, 87 males, aged 6 to 18 years) had two 24‐hour urine samples collected: the first sample at 1 year before bone measurement, and the second sample at the time of bone measurement. Major urinary GC metabolites were measured by mass spectrometry and summed to assess daily adrenal GC secretion (∑C21). Urinary free cortisol (UFF) and cortisone (UFE) were summed to assess potentially bioactive free GCs (UFF + UFE). After controlling for several covariates and especially urinary nitrogen (the biomarker of protein intake) cortisol secretion ∑C21 was inversely associated with all analyzed pQCT measures of bone quality. ∑C21 also predicted a higher endosteal and lower periosteal circumference, explaining both a smaller cortical area and (together with lower BMD) a lower strength‐strain‐index (SSI). UFF + UFE, UFE itself, and a urinary metabolite‐estimate of 11beta‐hydroxysteroid dehydrogenase type1 (11beta‐HSD1) activity showed corresponding reciprocal associations (p < 0.05) with BMD and bone mineral content, but not with SSI and bone geometry variables. In conclusion, higher GC levels, even within the physiological range, appear to exert negative influences on bone modeling and remodeling already during growth. Our physiological data also suggest a relevant role of cortisone as the direct source for intracrine‐generated cortisol by bone cell 11beta‐HSD1. © 2014 American Society for Bone and Mineral Research.